2021
DOI: 10.1038/s41598-021-86590-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic bacterial community response to Akashiwo sanguinea (Dinophyceae) bloom in indoor marine microcosms

Abstract: We investigated the dynamics of the bacterial composition and metabolic function within Akashiwo sanguinea bloom using a 100-L indoor microcosm and metagenomic next-generation sequencing. We found that the bacterial community was classified into three groups at 54% similarity. Group I was associated with “during the A. sanguinea bloom stage” and mainly consisted of Alphaproteobacteria, Flavobacteriia and Gammaproteobacteria. Meanwhile, groups II and III were associated with the “late bloom/decline stage to pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Generally, bacteria can promote the growth of HABs through the release of EPS (Jung et al, 2021;Kang et al, 2021) or inhibit HABs (Jung et al, 2008). Bacteria can utilize the EPS released by HABs and play important roles in biogeochemical cycling in oceans (Azam, 1998;Jung et al, 2021). Our results generally confirm previous reports (Grossart et al, 2005;Sapp et al, 2007), which found that phycospheres harbour host-specific bacteria based on the ability of bacteria to utilize different types of organic matter.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Generally, bacteria can promote the growth of HABs through the release of EPS (Jung et al, 2021;Kang et al, 2021) or inhibit HABs (Jung et al, 2008). Bacteria can utilize the EPS released by HABs and play important roles in biogeochemical cycling in oceans (Azam, 1998;Jung et al, 2021). Our results generally confirm previous reports (Grossart et al, 2005;Sapp et al, 2007), which found that phycospheres harbour host-specific bacteria based on the ability of bacteria to utilize different types of organic matter.…”
Section: Discussionsupporting
confidence: 89%
“…Bacterial communities can respond to phytoplankton blooms (Pinhassi et al, 2004), and HABs are known to be closely associated with host-specific bacteria (Mayali et al, 2011). Generally, bacteria can promote the growth of HABs through the release of EPS (Jung et al, 2021;Kang et al, 2021) or inhibit HABs (Jung et al, 2008). Bacteria can utilize the EPS released by HABs and play important roles in biogeochemical cycling in oceans (Azam, 1998;Jung et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations